The Effect of Religiousity and Subjective Norms on The Interest of Generation Z In Cash - Putra, Trisno Wardy; Winda, Winda; Nurwahida, Nurwahida; Sri Muntu, Andi Tenri; Wahyu, Muh. Nur (Jurnal Ar-Ribh, 2023)
This study focuses on analyzing the impact of religiosity and subjective norms on the interest of Generation Z in cash waqf. The purpose of this study is to analyze the behavior of generation Z in expanding interest in cash waqf as well as to see the role of waqf institutions as the main media in helping generation Z to make cash waqf. The method used is a quantitative research method. This study uses two types of data sources, namely primary data and secondary data. Primary data was obtained through the distribution of questionnaires and secondary data through library research such as journals, books, theses and others to strengthen the arguments in this study. The results showed that religiosity had a positive and significant impact on the interest of Generation Z in cash waqf. While subjective norms have a positive and insignificant effect on the interest of generation z in cash waqf.